MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN CONTEXTUAL TEACHING LEARNING SISWA KELAS VIIC SMP NEGERI 2 KALIBAWANG KULON PROGO - Wulandari Wulandari; AA Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The purpose of this study was to describe the process of learning by methods Contextual Teaching Learning (CTL) , increase interest and learning mathematics class VII C SMP Negeri 2 Kalibawang Kulon Progo. Hypothesis action in this study is through the implementation of cooperative learning approach can enhance CTL interest and learning outcomes. This research a Classroom Action Research (CAR) or Classroom Action research (CAR) conducted collaborative. The research suggests that increased student interest in each cycle by using learning methods Contextual Teaching Learning (CTL) compared to interest student learning before this research. Before this action student interest is the percentage of 32 % is included in the less qualified, student interest after the first cycle was 57 % qualify as moderate, while the students' interest after the second cycle was 79 % including higher qualifications. prior research These students passively listening to the teacher but after more research students actively ask questions and discuss the students' scores increased, the first score of 55.80 , an increase in the first cycle was 68.54 and increase the second cycle was 72.0. From the above results it shows that the model of learning Contextual Teaching Learning (CTL) may increase interest and student learning outcomes.